Processing of Unattended Emotional Facial Expressions: Correlates of Visual Field Bias in Women - Wittfoth, Dina; Preibisch, Christine; Lanfermann, Heinrich (Frontiers in Neuroscience, 2017)
Lateralization in emotional processing is a matter of ongoing debate. Various factors can influence lateralized emotional processing, including stimulus location, emotional valence and gender. In the present study, we aim to elucidate how unattended emotional facial expressions shown at different locations in the visual field influence behavioral responses, eye movement and neural responses in a sample of healthy women. Our female participants viewed fearful, happy and neutral faces presented at central and peripheral (left or right) locations while keeping their gaze locked on a central fixation crosshairs and indicating stimulus location via button presses. Throughout the experiment, we monitored fixation and gaze shifts by means of eye tracking. We analyzed eye movements, neural and behavioral responses from n=18 participants with excellent tracking and task performance. Face stimuli presented in the left hemifield entailed the fastest reactions irrespective of face valence. Unwarranted gaze shifts away from central fixation were rare and mainly directed at peripherally presented stimuli. A distributed neural network comprising the right amygdala, left temporal pole, left middle temporal gyrus, right superior frontal gyrus and right posterior putamen differentially responded to centrally presented fearful faces, and to peripherally presented neutral and happy faces, especially when they appeared in the left hemifield. Our findings point to a visual field bias on the behavioral and neural level in our female sample. Reaction times, eye movements and neural activations varied according to stimulus location. An interactive effect of face location with face valence was present at the neural level but did not translate to behavioral or eye movement responses.